2021
DOI: 10.1002/cac2.12156
|View full text |Cite
|
Sign up to set email alerts
|

The role of myeloid‐derived suppressor cells in gastrointestinal cancer

Abstract: Gastrointestinal (GI) cancer encompasses a range of malignancies that originate in the digestive system, which together represent the most common form of cancer diagnosed worldwide. However, despite numerous advances in both diagnostics and treatment, the incidence and mortality rate of GI cancer are on the rise. Myeloid‐derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that increase in number under certain pathological conditions, such as infection and inflammation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 187 publications
(180 reference statements)
0
19
0
Order By: Relevance
“…M-MDSCs are considered to show even more suppressive functions via high expression of Arg1, driving T cell anergy by depleting arginine pools. In addition, MDSCs can secrete high levels of IL-10 and TGF-beta, IFN-gamma [ 166 ] and produce reactive nitrogen species, negatively affecting T cell recruitment and activation [ 167 ]. They also exhibit tumor-promoting functions independent of immune suppression, such as the promotion of metastasis and angiogenesis via the production of VEGF, basic fibroblast growth factor (bFGF), and matrix metalloproteinase 9 (MMP9) [ 168 , 169 ].…”
Section: Reviewmentioning
confidence: 99%
“…M-MDSCs are considered to show even more suppressive functions via high expression of Arg1, driving T cell anergy by depleting arginine pools. In addition, MDSCs can secrete high levels of IL-10 and TGF-beta, IFN-gamma [ 166 ] and produce reactive nitrogen species, negatively affecting T cell recruitment and activation [ 167 ]. They also exhibit tumor-promoting functions independent of immune suppression, such as the promotion of metastasis and angiogenesis via the production of VEGF, basic fibroblast growth factor (bFGF), and matrix metalloproteinase 9 (MMP9) [ 168 , 169 ].…”
Section: Reviewmentioning
confidence: 99%
“…The high frequency of MDSCs was shown to be associated with a poor prognosis with various malignant neoplasms via the immunosuppressive effect in the tumor-associated immune system [11,12]. While the association between the total MDSC subsets and OS in PC patients has been reported in an earlier study [15], no studies have examined the impact of each of the MDSC subsets on the prognosis of patients with mHSPC.…”
Section: Prognostic Value Of Mdscs For Patients With Mhspcmentioning
confidence: 99%
“…In head and neck canner and ovarian cancer, it has been reported that e-MDSCs have an immunosuppressive property, but their speci c roles are still uncertain in other tumors [10]. It has been reported that the high frequency of MDSCs in peripheral blood is associated the disease progression and poor prognosis of many malignant neoplasms, including lung cancer and gastric cancer [11,12]. The several studies which have shown the role of MDSCs in localized PC or CRPC have been mainly focused on either PMN-MDSCs or M-MDSCs, however, there have been no reports on the involvement of the three MDSC subsets in untreated metastatic PC patients [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…CCR2 is mainly expressed on specific cell types, such as monocytes, NK, T cells, and MDSCs, particularly for the subset of M-MDSCs [101,102]. CCR2 binds with several ligands (i.e., CCL2, CCL7, CCL8, and CCL12), with the most potent binding preference with CCL2 [101].…”
Section: Prevention Of Mdscs Traffickingmentioning
confidence: 99%